Investigations of amination reactions on an antimalarial 1,2,4-triazolo[4,3-a]pyrazine scaffold - Henry S. T. Smith; Ben Giuliani; Kanchana Wijesekera; Kah Yean Lum; Sandra Duffy; Aaron Lock; Jonathan M. White; Vicky M. Avery; Rohan A. Davis (Beilstein Journal of Organic Chemistry)
1,2,4-Triazolo[4,3-a]pyrazines have previously been explored by the Open Source Malaria project as potent in vitro and in vivo antimalarial drug leads. With a view to generating a library of unique antimalarial 1,2,4-triazolo[4,3-a]pyrazines and exploring regiochemical preference for nucleophilic amines, we utilised the known synthetic 5-chloro-3-(4-chlorophenyl)-[1,2,4]triazolo[4,3-a]pyrazine (1) as a scaffold for aminations with 14 commercially available primary amines. Reacting scaffold 1 with excess primary amine at room temperature for 16 h generated the desired amine analogues in respectable yields (18–87%) and high purity (≥95%) following chromatography workup. The structures of the 14 previously undescribed amine analogues 2–15 were fully characterised following 1D/2D NMR, UV, and HRMS data analyses. X-ray crystallographic analysis of crystals obtained from the aminated products 2, 7, 10, and 15 are also reported here. The new library of amine-substituted triazolopyrazines was screened against the Plasmodium falciparum 3D7 strain. The tertiary alkylamine products 10–14 displayed antimalarial activity with IC50 values ranging from 9.90 to 23.30 µM against P. falciparum 3D7, with compounds 10–12 demonstrating no toxicity at 80 µM against the human embryonic kidney cell line HEK293.